Power losses minimization for modular multilevel converters with second‐order and fourth‐order harmonic circulating current injection. (9th June 2021) - Zhao, Jifeng; Deng, Fujin; Liu, Chengkai; Yu, Qiang
Summary: Modular multilevel converters (MMCs) are regarded as promising topologies in medium/high‐voltage and high‐power applications. The reduction of power losses is an important issue for MMCs. This paper proposes a power loss minimization control (PLMC) by injecting optimal second‐ and fourth‐order harmonic circulating current into the arm current of MMCs. The proposed control can further reduce the power loss in comparison with the conventional control by only injecting the second‐order harmonic circulating current. In addition, the proposed control not only reduces the peak value of the arm current, but also improves the reliability of MMCs. Simulation with the PSCAD/EMTDC and experiment with 1‐kW MMC prototype are also conducted and their results confirm the validity of the proposed PLMC for MMCs. Abstract : This paper proposes a power loss minimization control by injecting optimal second‐ and fourth‐order harmonic circulating current into the arm current of MMCs which can further reduce the power loss in comparison with the conventional control. In addition, the proposed control not only reduces the peak value of the arm current, but also improves the reliability of MMCs.